2021
DOI: 10.4314/ahs.v21i2.5
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial profile and their antimicrobial susceptibility patterns in patients admitted at MaddaWalabu University Goba Referral Hospital, Ethiopia: a cross sectional study

Abstract: Background: Hospital acquired infections (HAIs) are one of the global concerns in resource limited settings. The aim of the study was to determine bacteria profile and their antimicrobial susceptibility patterns among patients admitted at surgical and medical wards. Methods: A hospital based cross-sectional study was conducted from November 2016 to July 2017 in MaddaWalabu Uni- versity Goba Referral Hospital. Urine and wound swabs were processed and standard disk diffusion test was done to assess suscept… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 26 publications
2
1
0
Order By: Relevance
“…This was mainly due to the sharp increase in motorcycle accidents in Kenya, which mainly affects males [ 22 ]. Gram-negative bacteria were the more dominant isolates similar to other studies conducted in Africa [ 21 , 23 ]. Overall, coagulase-negative Staphylococci were the most isolated bacterial isolates, comparable to other studies that indicate CONS as the most commonly isolated microorganisms in clinical settings [ 24 ].…”
Section: Discussionsupporting
confidence: 85%
“…This was mainly due to the sharp increase in motorcycle accidents in Kenya, which mainly affects males [ 22 ]. Gram-negative bacteria were the more dominant isolates similar to other studies conducted in Africa [ 21 , 23 ]. Overall, coagulase-negative Staphylococci were the most isolated bacterial isolates, comparable to other studies that indicate CONS as the most commonly isolated microorganisms in clinical settings [ 24 ].…”
Section: Discussionsupporting
confidence: 85%
“…Among the positive samples, those associated with females were less than those from male's contrary to other studies which demonstrated more samples from females than males (20). This was mainly due to the sharp increase in motor cycle accidents in Kenya, which mainly affects males (21). Gram-negative bacteria were the more dominant isolates similar to other studies conducted in Africa (20) (22).…”
Section: Discussionsupporting
confidence: 79%
“…Tis recognized prevalence of GPB might be due to the bacterial resistance ability to dry conditions of the hospital environment and transmission from skin, nasal, and hands of health care providers and patients, and also the presence of underlying clinical conditions and immunocompromised patients admitted to intensive care. From Gram-negative isolates, E. coli 41 (39%) was highly isolates from the all study groups in these output, but it contradicts with the fndings of the study in Namibia 24% [30], Gondar 16.3%, [34], Madda-Walabu 20.9% [39], Mizan-Tepi 11.4% [36], Gondar [34], Northern Nigeria 8.0% [40], Mekelle 0.8%, [27] and Hiwot Fana 7.3% [41]. Tis could be explained by existence of colonized/infected patients in the ICU environments of the hospital, or failure of routine cleaning and disinfection practices.…”
Section: Discussionmentioning
confidence: 61%